Prediction of destination at discharge from a comprehensive rehabilitation hospital using the home care score - Tani, Keisuke; Oku, Kosuke; Nomura, Shohei; Tamaru, Yoshiki; Matsugi, Akiyoshi; Nagano, Kiyoshi; Yoshioka, Nami; Murakami, Yoshikazu; Yamashita, Akira; Mori, Nobuhiko (Journal of Physical Therapy Science, 2016)
[Purpose] This study investigated whether it is possible to predict return to home at discharge from a rehabilitation hospital in Japan using the home care score of patients with cerebrovascular or osteoarticular disease and low activities of daily living at admission. [Subjects and Methods] The home care score and functional independent measurement were determined for 226 patients at admission and at discharge from five hospitals, and receiver operating characteristic analyses were conducted. [Results] The home care score cutoff point for the prediction of return to home at admission and at discharge was 11, and the area under the curve was more than 0.8. The area under the curve of the home care score was 0.77 for patients with low activities of daily living and within this group, the probability of return to home was approximately 50%, as predicted by the functional independent measurement. The home care score increased after receiving intervention at a rehabilitation hospital. [Conclusion] The home care score is useful for the prediction of return to home from a rehabilitation hospital, although prediction using the functional independent measurement is difficult for patients with low activities of daily living. Moreover, comprehensive interventions provided by the rehabilitation hospitals improve the ability to provide home care of the patient’s family, which is assessed by the home care score.